Fiddler crabs can feel more than we think: the influence of neighbors on the activities of the fiddler crab Leptuca uruguayensis - Martins, Carolina Guardino [UNESP]; De Grande, Fernando Rafael; Costa, Tânia Marcia [UNESP] (Springer Nature, 2024)
Fiddler crabs have been used as model organisms in many laboratory and field studies. In their natural environment, social interaction with other fiddler crabs (conspecific or heterospecific) is recurrent, but manipulative studies involving these crabs as models are often performed with isolated individuals. The isolation of an animal can interfere in the behaviors recorded as response variables. Thus, the aim of this study was to evaluate whether the presence of other individuals affects the performance of behaviors of fiddler crabs Leptuca uruguayensis. We tested two hypotheses in the field: (1) the visual stimulus of the crab assemblage affects the activity of male fiddler crabs; and (2) the presence of other conspecific affects the activity of male fiddler crabs depending on the sexes of the individuals present. We found the activities of L. uruguayensis males mediated by social interactions does not depend exclusively on visual stimuli. Physical interaction with other conspecifics of both sexes enables the perception of stimuli which can influence the waving behavior of L. uruguayensis males. We suggest that behavioral studies with this model should consider the presence of other individuals. Understanding the behavioral complexity of a model organism contributes to more robust experiments with greater control of interfering variables.
Keywords: Animal behavior; Animal communication; Animal testing; Intertidal zone; Mangrove ecosystem